A pitch-based hard carbon composite material and preparation method thereof and sodium ion battery

By co-doping tin and phosphorus elements into the core hard carbon of the negative electrode material of sodium ion battery and coating the composite layer of fast ion conductor of sodium, the problem of insufficient energy density and power performance of existing materials is solved, and high energy density and 优异的快充性能。

CN118553899BActive Publication Date: 2025-02-07GUOKE TANMEI NEW MATERIALS (HUZHOU) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411019235.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2025-02-07
Estimated Expiration
2044-07-29

AI Technical Summary

Technical Problem

The energy density and power performance of existing sodium ion battery negative electrode materials are insufficient, making it difficult to meet the needs of high energy density fast charging.

Method used

Co-doped tin and phosphorus elements in the core hard carbon and coated with sodium on its surface to improve the specific capacity and rate performance of the material.

Benefits of technology

It significantly improves the specific capacity and rate performance of the material, improves the first-time efficiency and fast charging performance, and achieves the goal of high energy density and excellent power performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118553899B_ABST
    Figure CN118553899B_ABST
Patent Text Reader

Abstract

The present invention provides an asphalt-based hard carbon composite material, a preparation method thereof and a sodium ion battery, and belongs to the technical field of battery materials. The asphalt-based hard carbon composite material is a core-shell structure, the core is a hard carbon co-doped with phosphorus and tin, and the outer shell is a sodium fast ion conductor composite layer. The present invention co-dopes tin and phosphorus elements in the hard carbon core, and the two cooperate with each other to significantly improve the specific capacity of the material. At the same time, the sodium fast ion conductor composite layer is coated, and the rate performance and the first efficiency of the material are effectively improved by relying on its high ionic conductivity. The asphalt-based hard carbon composite material has high energy density and excellent power performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to an asphalt-based hard carbon composite material, a preparation method thereof, and a sodium ion battery. Background Art

[0002] As the market demands for fast charging performance and energy density of sodium-ion batteries, the hard carbon used in the negative electrode materials of sodium-ion batteries is required to have high specific capacity and compaction density. Currently, the specific capacity of commercialized hard carbon is about 300mAh / g, and the compaction density is about 1.0g / cm 3 , resulting in a low energy density of the material, and a charging capacity of ≤1C, which is difficult to meet the needs of high energy density fast charging sodium ion fast charging. The materials such as phosphorus / molybdenum compounds and tin compounds can form alloy materials with sodium during the charging and discharging process to improve the specific capacity of the material, but the full charge expansion of the material during the charging and discharging process is high, and the low first efficiency limits its application. Therefore, it is necessary to coat it to improve the diffusion rate, first efficiency and fast charging performance of the material. For example, patent CN115991467A discloses an oxidized asphalt-based hard carbon negative electrode material for sodium ion batteries and a preparation method thereof, the preparation method comprising: crushing the asphalt to obtain crushed asphalt; using a fluidized bed to adjust the temperature to oxidize the crushed asphalt to obtain an oxidized precursor; the oxidized precursor is sieved and subjected to high-temperature carbonization treatment to prepare an oxidized asphalt-based hard carbon negative electrode material for sodium ion batteries. Although the specific capacity has been improved, the specific capacity improvement is not large, the power performance deviation, and the first efficiency is low.

[0003] Therefore, how to significantly improve the energy density and power performance of hard carbon materials is a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a pitch-based hard carbon composite material, a preparation method thereof and a sodium ion battery. The present invention co-dopes tin and phosphorus elements in the core hard carbon, and the two cooperate with each other to significantly improve the specific capacity of the material. At the same time, the fast ion conductor composite layer of sodium is coated, and the high ion conductivity of the material is relied on to effectively improve the rate performance and the first efficiency of the material. The pitch-based hard carbon composite material has high energy density and excellent power performance.

[0005] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a pitch-based hard carbon composite material, wherein the pitch-based hard carbon composite material is a core-shell structure, wherein the core is phosphorus-tin co-doped hard carbon, and the shell is a sodium fast ion conductor composite layer.

[0007] The present invention co-doped tin and phosphorus elements in the core hard carbon, and the two cooperated with each other to significantly improve the specific capacity of the material, and at the same time coated with a sodium fast ion conductor composite layer, relying on its high ion conductivity, effectively improved the rate performance and initial efficiency of the material. The pitch-based hard carbon composite material has high energy density and excellent power performance.

[0008] In the present invention, the doping of tin element can rely on the sodium tin formed during the charge and discharge process to increase the specific capacity of the material. The sodium tin cooperates with the phosphorus element to effectively increase the specific capacity of the material and its structural stability, and improve the cycle performance.

[0009] Preferably, the total doping amount of the phosphorus-tin co-doping accounts for 5-15% of the mass of the core, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%.

[0010] In the present invention, if the total doping amount of phosphorus and tin co-doping is too small, the improvement of the material specific capacity will be limited; if the total doping amount of phosphorus and tin co-doping is too large, the compaction density of the material will be reduced.

[0011] Preferably, in the inner core, the mass ratio of phosphorus element to tin element is 1:(0.5-2), for example, it can be 1:0.5, 1:1 or 1:2.

[0012] In the present invention, if the mass ratio of phosphorus to tin is too small, the phosphorus content of the material will be low, reducing the specific capacity of the material; if the mass ratio of phosphorus to tin is too large, that is, the amount of tin added is too small, the power performance of the material will be limited.

[0013] Preferably, the core is further doped with heteroatoms, and the heteroatoms include nitrogen atoms.

[0014] In the present invention, doping with heteroatoms is beneficial to improving the electronic conductivity of the material.

[0015] Preferably, based on the mass of the pitch-based hard carbon composite material, the mass content of the shell is 5-15%, for example, 5%, 7%, 10%, 12% or 15%.

[0016] Preferably, the sodium fast ion conductor composite layer includes at least one layer, for example, it can be 10 layers, 30 layers, 50 layers, 70 layers, 100 layers, 150 layers or 200 layers, etc., preferably 50-150 layers.

[0017] In the present invention, a multi-layer sodium fast ion conductor composite layer is used to construct the shell, which is more conducive to improving the transmission rate of sodium ions during charging and discharging, improving rate performance, reducing defects in the material core, and improving the initial efficiency.

[0018] Preferably, the sodium fast ion conductor composite layer comprises a fast ion conductor material and a binder.

[0019] Preferably, the chemical formula of the fast ion conductor material is NaX a PO4(MoO4) b , wherein X is any one of Fe, Mn, Sn, Sr or Ce or a combination of at least two thereof, 1≤a≤4, for example, it can be 1, 2, 3 or 4, etc., 1≤b≤4, for example, it can be 1, 2, 3 or 4, etc.

[0020] The fast ion conductor material used in the present invention can better improve the ion transfer rate during the charge and discharge process and improve the rate performance of the material compared to NaTi2(PO)3, Na3V2(PO4)3 or NaZr2(PO4)3 in the prior art. The fast ion conductor material has good compatibility with sodium ion electrolyte and can effectively improve the cycle and storage performance of sodium ion batteries.

[0021] Preferably, the binder comprises sodium carboxymethylcellulose.

[0022] Preferably, the mass ratio of the fast ion conductor material to the binder is (8-12):1, for example, it can be 8:1, 9:1, 10:1, 11:1 or 12:1.

[0023] In a second aspect, the present invention provides a method for preparing the pitch-based hard carbon composite material as described in the first aspect, the preparation method comprising the following steps:

[0024] (1) mixing oxidized asphalt, a tin source, an oxidant and an organic solvent, and performing a hydrothermal reaction to obtain a tin-doped hard carbon precursor material;

[0025] (2) mixing the tin-doped hard carbon precursor material and a phosphorus source, and reacting them to obtain a tin phosphide-doped hard carbon composite material;

[0026] (3) coating the surface of the tin phosphide-doped hard carbon composite material with a sodium fast ion conductor composite material to obtain the asphalt-based hard carbon composite material.

[0027] The present invention does not limit the preparation method of oxidized asphalt. For example, the oxidized asphalt can be prepared by the following method:

[0028] The asphalt raw material is transferred to a rotary kiln, and the temperature is raised to 200-250°C (for example, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C) at a heating rate of 1-10°C / min (for example, 1°C / min, 3°C / min, 5°C / min, 7°C / min or 9°C / min, etc.), and air is introduced for 1-6h (for example, 1h, 2h, 3h, 4h, 5h or 6h, etc.) to obtain oxidized asphalt. The asphalt raw material can be any one of petroleum asphalt, coal asphalt or mesophase asphalt, or a combination of at least two of them.

[0029] Preferably, the tin source in step (1) comprises a tin salt.

[0030] Preferably, the tin salt includes any one of stannous oleate, tin stearate, stannous oxalate, stannous oxalate, tin pyrophosphate, tin methanesulfonate, dibutyltin diacetate, dioctyltin distearate, tin 2-ethylhexanoate, tributyltin salicylate or tributyltin acetate, or a combination of at least two thereof.

[0031] Preferably, the oxidant in step (1) comprises hydrogen peroxide and / or peracetic acid.

[0032] Preferably, the organic solvent in step (1) comprises any one of carbon tetrachloride, n-hexane, xylene or carbon disulfide, or a combination of at least two thereof.

[0033] Preferably, in step (1), the mass ratio of the oxidized asphalt, the tin source, the oxidant and the organic solvent is 100:(1-10):(5-15):(500-1500), wherein the selection range of the tin source "1-10" can be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, the selection range of the oxidant "5-15" can be, for example, 5, 6, 7, 8, 9, 10, 11, 12, 13 or 14, and the selection range of the organic solvent "500-1500" can be, for example, 500, 750, 1000, 1250 or 1500, etc.

[0034] Preferably, a heteroatom compound is also added during the mixing process in step (1).

[0035] Preferably, the heteroatom compound includes any one of 4-methylthiosemicarbazide, diaminothiourea or malonylthiourea, or a combination of at least two thereof.

[0036] Preferably, the mass ratio of the heteroatom compound to the tin source is (1-10):(1-10), wherein the selection range of the heteroatom compound "1-10" can be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, and the selection range of the tin source "1-10" can be, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10, etc.

[0037] Preferably, the temperature of the hydrothermal reaction in step (1) is 80-150°C, for example, 80°C, 100°C, 120°C or 150°C, and the time is 1-6h, for example, 1h, 2h, 3h, 4h, 5h or 6h.

[0038] Preferably, drying is further performed after the hydrothermal reaction is completed, and the drying is freeze-drying.

[0039] Preferably, the phosphorus source in step (2) is a phosphorus-containing gas, and the phosphorus-containing gas includes red phosphorus gas.

[0040] Preferably, the gas flow rate of the phosphorus-containing gas is 100-500 mL / min, for example, 100 mL / min, 200 mL / min, 300 mL / min, 400 mL / min or 500 mL / min.

[0041] Preferably, the reaction temperature in step (2) is 500-800°C, for example, 500°C, 600°C, 700°C or 800°C, and the reaction time is 60-600 min, for example, 60 min, 100 min, 200 min, 300 min, 400 min, 500 min or 600 min.

[0042] In the present invention, if the reaction temperature is too low, the red phosphorus gas is not completely gasified, which affects the deposition efficiency; if the reaction temperature is too high, the deposition efficiency is too fast, which reduces the deposition quality.

[0043] Preferably, after the reaction in step (2) is completed, a cross-linking gas is introduced to carry out cross-linking and curing.

[0044] In the present invention, the purpose of introducing the cross-linking gas is to create pores and increase the specific capacity of the material.

[0045] Preferably, the cross-linking gas includes any one of acetic acid peroxide gas, cyclohexanone peroxide gas, butanone peroxide gas or lauroyl peroxide gas, or a combination of at least two thereof.

[0046] Preferably, the gas flow rate of the cross-linking gas is 100-500 mL / min, for example, 100 mL / min, 200 mL / min, 300 mL / min, 400 mL / min or 500 mL / min.

[0047] Preferably, the cross-linking curing temperature is 500-800°C, for example, 500°C, 600°C, 700°C or 800°C, and the time is 60-600min, for example, 60min, 100min, 200min, 300min, 400min, 500min or 600min.

[0048] Preferably, the coating method in step (3) comprises atomic layer deposition.

[0049] Preferably, during the coating process in step (3), the ambient temperature is 300-400°C, for example, 300°C, 320°C, 340°C, 360°C, 380°C or 400°C.

[0050] In the present invention, if the coating temperature is too low, impurities such as incompletely volatilized materials will exist in the coating layer material, and its structure will be unstable, reducing the cycle performance of the material; if the coating temperature is too high, the structure of the material will change, reducing the cycle performance.

[0051] Preferably, the preparation method comprises the following steps:

[0052] (1) After dissolving the oxidized asphalt in an organic solvent, adding a heteroatom compound and a tin source to disperse uniformly, then dropping an oxidant to mix, performing a hydrothermal reaction at 80-150° C. for 1-6 hours, filtering, and freeze-drying to obtain a tin-doped hard carbon precursor material;

[0053] Wherein, the mass ratio of oxidized asphalt, tin source, heteroatom compound, oxidant and organic solvent is 100:(1-10):(1-10):(5-15):(500-1500);

[0054] (2) heating the tin-doped hard carbon precursor material to 500-800° C., introducing a phosphorus-containing gas at a flow rate of 100-500 mL / min for 60-600 min, and then introducing a cross-linking gas at a flow rate of 100-500 mL / min for 60-600 min to obtain a tin phosphide-doped hard carbon composite material;

[0055] (3) The tin phosphide-doped hard carbon composite material is placed in a reaction chamber, evacuated, and then heated to 300-400°C, and a sodium fast ion conductor composite material is cyclically deposited (for example, 50-150 cycles, such as 50 cycles, 100 cycles or 150 cycles, etc.) on the surface of the tin phosphide-doped hard carbon composite material to form at least one layer of sodium fast ion conductor composite layer. After the cyclic deposition is completed, the chamber is cooled to obtain the asphalt-based hard carbon composite material.

[0056] In a third aspect, the present invention provides a sodium ion battery, wherein the negative electrode of the sodium ion battery comprises the asphalt-based hard carbon composite material as described in the first aspect.

[0057] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0058] Compared with the prior art, the present invention has the following beneficial effects:

[0059] The present invention co-doped tin and phosphorus elements in the core hard carbon, and the two cooperated with each other to significantly improve the specific capacity of the material, and at the same time coated with a sodium fast ion conductor composite layer, relying on its high ion conductivity, effectively improved the rate performance and initial efficiency of the material. The pitch-based hard carbon composite material has high energy density and excellent power performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 This is a SEM image of the asphalt-based hard carbon composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0061] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0062] Example 1

[0063] This embodiment provides a pitch-based hard carbon composite material, wherein the pitch-based hard carbon composite material is a core-shell structure, wherein the core is a phosphorus-tin co-doped hard carbon, and the shell is a sodium fast ion conductor composite layer;

[0064] The total doping amount of the phosphorus-tin co-doping accounts for 10% of the mass of the core; in the core, the mass ratio of phosphorus element to tin element is 1:1; the core is also doped with nitrogen atoms;

[0065] Based on the mass of the asphalt-based hard carbon composite material, the mass content of the shell is 10%;

[0066] The number of layers of the sodium fast ion conductor composite layer is 100;

[0067] The sodium fast ion conductor composite layer includes a fast ion conductor material and a binder, the general chemical formula of the fast ion conductor material is NaFe2PO4(MoO4), and the binder is sodium carboxymethyl cellulose, and the mass ratio of the two is 10:1.

[0068] This embodiment also provides a method for preparing the above-mentioned pitch-based hard carbon composite material, the preparation method comprising the following steps:

[0069] (1) The petroleum asphalt is transferred to a rotary kiln and heated to 220°C at a heating rate of 5°C / min, and air is introduced to keep the temperature for 3 hours to obtain oxidized asphalt;

[0070] (2) After dissolving 100 g of oxidized asphalt in 1000 g of organic solvent carbon tetrachloride, 5 g of heteroatom compound 4-methylthiosemicarbazide and 5 g of stannous oleate were added and dispersed evenly, and then 10 g of hydrogen peroxide was added dropwise to mix, and then transferred to a high-pressure reactor, and a hydrothermal reaction was carried out at 120°C for 3 h, filtered, and freeze-dried at -40°C for 24 h to obtain a tin-doped hard carbon precursor material;

[0071] The mass ratio of oxidized asphalt, stannous oleate, 4-methylthiosemicarbazide, hydrogen peroxide and carbon tetrachloride is 100:5:5:10:1000;

[0072] (3) transferring the tin-doped hard carbon precursor material to a rotary kiln, heating it to 650° C., introducing red phosphorus gas at a flow rate of 300 mL / min for 300 min, and then changing to peracetic acid gas at a flow rate of 300 mL / min for 300 min to obtain a tin phosphide-doped hard carbon composite material;

[0073] (4) The tin phosphide-doped hard carbon composite material is placed in a reaction chamber, evacuated to 0.1 torr, and then heated to 350°C, and a sodium fast ion conductor composite material (including NaFe2PO4(MoO4) and sodium carboxymethyl cellulose in a mass ratio of 10:1) is cyclically deposited on the surface of the tin phosphide-doped hard carbon composite material. The specific process includes: 1) introducing the sodium fast ion conductor composite material for 0.3 seconds; 2) nitrogen purging for 60 seconds; 3) introducing oxygen for 5 seconds; 4) nitrogen purging for 5 seconds; 5) introducing water vapor for 0.03 seconds; 6) nitrogen purging for 50 seconds; 7) starting from step 1), the cycle is repeated 100 times to form a fast ion conductor composite layer. After the cyclic deposition is completed, the mixture is cooled to room temperature of 25°C to obtain the asphalt-based hard carbon composite material.

[0074] Figure 1 The SEM image of the asphalt-based hard carbon composite material prepared in this embodiment is shown. It can be seen from the image that the asphalt-based hard carbon composite material has a granular structure with a particle size between 3-7µm.

[0075] Example 2

[0076] This embodiment provides a pitch-based hard carbon composite material, wherein the pitch-based hard carbon composite material is a core-shell structure, wherein the core is a phosphorus-tin co-doped hard carbon, and the shell is a sodium fast ion conductor composite layer;

[0077] The total doping amount of the phosphorus-tin co-doping accounts for 5% of the mass of the core; in the core, the mass ratio of phosphorus element to tin element is 1:0.5; the core is also doped with nitrogen atoms;

[0078] Based on the mass of the asphalt-based hard carbon composite material, the mass content of the shell is 5%;

[0079] The number of layers of the sodium fast ion conductor composite layer is 50;

[0080] The sodium fast ion conductor composite layer includes a fast ion conductor material and a binder, the general chemical formula of the fast ion conductor material is NaSn2PO4(MoO4), and the binder is sodium carboxymethyl cellulose, and the mass ratio of the two is 10:1.

[0081] This embodiment also provides a method for preparing the above-mentioned pitch-based hard carbon composite material, the preparation method comprising the following steps:

[0082] (1) The petroleum asphalt is transferred to a rotary kiln and heated to 200°C at a heating rate of 1°C / min, and air is introduced for 6 hours to obtain oxidized asphalt;

[0083] (2) After dissolving 100 g of oxidized asphalt in 500 g of organic solvent n-hexane, 1 g of heteroatom compound diaminothiourea and 1 g of tin stearate were added and dispersed evenly, and then 5 g of hydrogen peroxide was added dropwise to mix, and then transferred to a high-pressure reactor, and a hydrothermal reaction was carried out at 80 ° C for 6 h, filtered, and freeze-dried at -40 ° C for 24 h to obtain a tin-doped hard carbon precursor material;

[0084] The mass ratio of oxidized asphalt, tin stearate, diaminothiourea, hydrogen peroxide and n-hexane is 100:1:1:5:500;

[0085] (3) transferring the tin-doped hard carbon precursor material to a rotary kiln, heating it to 500° C., introducing red phosphorus gas at a flow rate of 100 mL / min for 600 min, and then introducing cyclohexanone peroxide gas at a flow rate of 100 mL / min for 600 min to obtain a tin phosphide-doped hard carbon composite material;

[0086] (4) The tin phosphide-doped hard carbon composite material is placed in a reaction chamber, evacuated to 0.1 torr, and then heated to 300°C, and a sodium fast ion conductor composite material (including NaSn2PO4(MoO4) and sodium carboxymethyl cellulose in a mass ratio of 10:1) is cyclically deposited on the surface of the tin phosphide-doped hard carbon composite material. The specific process includes: 1) introducing the sodium fast ion conductor composite material for 0.3 seconds; 2) nitrogen purge for 60 seconds; 3) introducing oxygen for 5 seconds; 4) nitrogen purge for 5 seconds; 5) introducing water vapor for 0.03 seconds; 6) nitrogen purge for 50 seconds; 7) starting from step 1), the cycle is repeated 50 times to form a fast ion conductor composite layer. After the cyclic deposition is completed, the mixture is cooled to room temperature of 25°C to obtain the asphalt-based hard carbon composite material.

[0087] Example 3

[0088] This embodiment provides a pitch-based hard carbon composite material, wherein the pitch-based hard carbon composite material is a core-shell structure, wherein the core is a phosphorus-tin co-doped hard carbon, and the shell is a sodium fast ion conductor composite layer;

[0089] The total doping amount of the phosphorus-tin co-doping accounts for 15% of the mass of the core; in the core, the mass ratio of phosphorus element to tin element is 1:2; the core is also doped with nitrogen atoms;

[0090] Based on the mass of the asphalt-based hard carbon composite material, the mass content of the shell is 15%;

[0091] The number of layers of the sodium fast ion conductor composite layer is 150;

[0092] The sodium fast ion conductor composite layer includes a fast ion conductor material and a binder, the general chemical formula of the fast ion conductor material is NaCe2PO4(MoO4), and the binder is sodium carboxymethyl cellulose, and the mass ratio of the two is 10:1.

[0093] This embodiment also provides a method for preparing the above-mentioned pitch-based hard carbon composite material, the preparation method comprising the following steps:

[0094] (1) The petroleum asphalt is transferred to a rotary kiln and heated to 250°C at a heating rate of 10°C / min, and air is introduced and kept at this temperature for 1 hour to obtain oxidized asphalt;

[0095] (2) After dissolving 100 g of oxidized asphalt in 1500 g of an organic solvent, xylene, 10 g of a heteroatom compound, malonylthiourea and 10 g of stannous oxalate were added and dispersed evenly, and then 15 g of hydrogen peroxide was added dropwise to mix, and then the mixture was transferred to a high-pressure reactor and subjected to a hydrothermal reaction at 150 ° C for 11 h, filtered, and freeze-dried at -40 ° C for 24 h to obtain a tin-doped hard carbon precursor material;

[0096] The mass ratio of oxidized asphalt, stannous oxalate, malonylthiourea, hydrogen peroxide and xylene is 100:10:10:15:1500;

[0097] (3) transferring the tin-doped hard carbon precursor material to a rotary kiln, heating it to 800° C., introducing red phosphorus gas at a flow rate of 500 mL / min for 60 min, and then introducing butanone peroxide gas at a flow rate of 500 mL / min for 60 min to obtain a tin phosphide-doped hard carbon composite material;

[0098] (4) The tin phosphide-doped hard carbon composite material is placed in a reaction chamber, evacuated to 0.1 torr, and then heated to 400°C, and a sodium fast ion conductor composite material (including NaCe2PO4(MoO4) and sodium carboxymethyl cellulose in a mass ratio of 10:1) is cyclically deposited on the surface of the tin phosphide-doped hard carbon composite material. The specific process includes: 1) introducing the sodium fast ion conductor composite material for 0.3 seconds; 2) nitrogen purge for 60 seconds; 3) introducing oxygen for 5 seconds; 4) nitrogen purge for 5 seconds; 5) introducing water vapor for 0.03 seconds; 6) nitrogen purge for 50 seconds; 7) starting from step 1), the cycle is repeated 150 times to form a fast ion conductor composite layer. After the cyclic deposition is completed, the mixture is cooled to room temperature of 25°C to obtain the asphalt-based hard carbon composite material.

[0099] Example 4

[0100] The difference between this embodiment and embodiment 1 is that the amount of stannous oleate added and the time of introduction of red phosphorus gas are adjusted so that the total doping amount of phosphorus and tin co-doping accounts for 1% of the mass of the core.

[0101] The rest of the preparation methods and parameters were the same as those in Example 1.

[0102] Example 5

[0103] The difference between this embodiment and embodiment 1 is that the amount of stannous oleate added and the time of introduction of red phosphorus gas are adjusted so that the total doping amount of phosphorus and tin co-doping accounts for 20% of the mass of the core.

[0104] The rest of the preparation methods and parameters were the same as those in Example 1.

[0105] Example 6

[0106] The difference between this embodiment and embodiment 1 is that the general chemical formula of the fast ion conductor material is NaTi2(PO)3.

[0107] The rest of the preparation methods and parameters were the same as those in Example 1.

[0108] Comparative Example 1

[0109] The difference between this comparative example and Example 1 is that step (4) is not performed, that is, coating with the sodium fast ion conductor composite layer is not performed.

[0110] The rest of the preparation methods and parameters were the same as those in Example 1.

[0111] Comparative Example 2

[0112] The difference between this comparative example and Example 1 is that 4-methylthiosemicarbazide and stannous oleate are not added in step (2).

[0113] The rest of the preparation methods and parameters were the same as those in Example 1.

[0114] Performance Testing

[0115] 1. Physical and chemical performance test

[0116] The asphalt-based hard carbon composite materials prepared in the above-mentioned embodiments and comparative examples were tested for specific surface area by using a specific surface area tester; the powder OI value was tested by XRD; the tap density was tested according to GB / T-43114-2023 "Hard Carbon"; the grain size La was calculated by XRD, and the powder resistivity was tested by four-probe test; and the diffusion coefficient of the powder material was tested by GITT.

[0117] 2. Electrochemical performance test of button battery

[0118] The asphalt-based hard carbon composite materials prepared in the above embodiments and comparative examples were assembled into button batteries, and the assembly method was as follows: 5g of binder, 5g of conductive agent and 220mL of solvent were added to 90g of asphalt-based hard carbon composite material, the mixture was stirred to make a slurry, and then coated on a copper foil, and the negative electrode was obtained after drying and rolling. The binder used was LA132 binder, the conductive agent was SP, and the solvent was double distilled water. The electrolyte was NaPF6 / (EC+DEC) (volume ratio of 1:1, concentration of 1.1 mol / L), the sodium sheet was the counter electrode, and the diaphragm was a polyethylene propylene (PEP) composite film, and the simulated battery assembly was carried out in an argon-filled glove box.

[0119] The electrochemical performance of the button battery was tested on a Wuhan Blue Electric CT2001A battery tester with a charge and discharge voltage range of 0.00V to 2.0V and a charge and discharge rate of 0.1C. The rate performance (1C / 0.1C) and cycle performance (0.2C / 0.2C, 100 times) were also tested.

[0120] The above test results are shown in Table 1.

[0121] Table 1

[0122]

[0123] It can be seen from Table 1 that compared with Comparative Examples 1-2, the first discharge capacity and first efficiency, rate performance and cycle performance of the asphalt-based hard carbon composite materials prepared in Examples 1-3 are significantly improved. The reason is that the asphalt-based hard carbon composite material provided by the present invention has a small resistivity; at the same time, the surface of the material is coated with a fast ion conductor composite layer of sodium, which improves the sodium ion diffusion rate of the material and reduces its defects, thereby effectively improving the first efficiency of the material and improving its rate and cycle performance.

[0124] It can be seen from Example 1 and Examples 4-5 that if the total doping amount of phosphorus-tin co-doping is too small, the specific capacity of the material will be reduced and its diffusion coefficient will be reduced, and the rate performance will deviate; if the total doping amount of phosphorus-tin co-doping is too large, the tap density of the material will be reduced and its cycle performance will be reduced.

[0125] It can be seen from Example 1 and Example 6 that the fast ion conductor material used in the present invention can obtain better rate performance and structural stability compared to NaTi2(PO)3 in the prior art, and significantly improves the cycle performance of the material.

[0126] 3. Electrochemical performance test of soft pack battery

[0127] The pitch-based hard carbon composite material prepared in the above examples and comparative examples was used as the negative electrode, and the negative electrode sheet was prepared by slurry mixing and coating. 1 / 3 Mn 1 / 3 Ni 1 / 3 A 5Ah soft-pack battery was prepared using O2) as the positive electrode, NaPF6 (the solvent is EC+DEC, the volume ratio is 1:1, the electrolyte concentration is 1.1 mol / L) as the electrolyte, and Celgard2400 membrane as the separator.

[0128] The 5Ah soft-pack battery was tested for rate performance and cycle performance.

[0129] Rate performance test: The charge and discharge voltage range is 1-4V, the test temperature is 25±3.0℃, charging is performed at 1.0C, 2.0C, and 3.0C, and discharging is performed at 1.0C, to test the constant current ratio of the battery under different charging modes.

[0130] Cyclic performance test: 500 charge and discharge cycles were performed at a charge and discharge rate of 1C / 1C and a voltage range of 1-4V to test its capacity retention rate and initial DCR.

[0131] The above test results are shown in Table 2.

[0132] Table 2

[0133]

[0134] It can be seen from Table 2 that the rate charging performance of the soft-pack batteries prepared in Examples 1-3 is significantly better than that of Comparative Examples 1-2, that is, the charging time is shorter, indicating that the asphalt-based hard carbon composite material prepared by the present invention has good fast charging performance. The reason may be that the electronic conductivity and diffusion coefficient of the material are significantly improved, thereby improving the rate performance of the material. In addition, the cycle performance of the soft-pack battery prepared by the present invention is better than that of the comparative example. The reason may be that the asphalt-based hard carbon composite material provided by the present invention has a large interlayer spacing and a low powder OI value, which is conducive to reducing expansion and improving cycle performance; at the same time, the fast ion conductor coated on the surface of the material improves the diffusion rate of sodium ions during charging and discharging, reduces its irreversible capacity loss, and thus improves the cycle performance.

[0135] It can be seen from Example 1 and Examples 4-5 that if the total doping amount of phosphorus-tin co-doping is too small, the diffusion coefficient of the material will deteriorate, reducing the rate performance; if the total doping amount of phosphorus-tin co-doping is too large, the diffusion coefficient of the material will be increased, causing the material to expand more and reduce the cycle performance.

[0136] It can be seen from Example 1 and Example 6 that the fast ion conductor material used in the present invention can better improve the structural stability of the material and improve the cycle performance compared to NaTi2(PO)3 in the prior art.

[0137] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A pitch-based hard carbon composite material, characterized in that: The pitch-based hard carbon composite material is a core-shell structure, wherein the core is hard carbon doped with tin phosphide and the shell is a fast ion conductor composite layer of sodium; The total doping amount of the tin phosphide doping accounts for 5-15% of the mass of the core; In the core, the mass ratio of phosphorus element to tin element is 1:(0.5-2); The sodium fast ion conductor composite layer includes a fast ion conductor material and a binder; The chemical formula of the fast ion conductor material is NaX a PO4(MoO4) b , wherein X is any one of Fe, Mn, Sn, Sr or Ce or a combination of at least two thereof, 1≤a≤4, 1≤b≤4.

2. The pitch-based hard carbon composite material according to claim 1, characterized in that: The core is further doped with heteroatoms, which include nitrogen atoms.

3. The pitch-based hard carbon composite material according to claim 1, characterized in that: Based on the mass of the asphalt-based hard carbon composite material, the mass content of the shell is 5-15%; The sodium fast ion conductor composite layer comprises at least one layer; The binder includes sodium carboxymethyl cellulose; The mass ratio of the fast ion conductor material to the binder is (8-12):

1.

4. A method for preparing a pitch-based hard carbon composite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing oxidized asphalt, a tin source, an oxidant and an organic solvent, and performing a hydrothermal reaction to obtain a tin-doped hard carbon precursor material; (2) mixing the tin-doped hard carbon precursor material and a phosphorus source, and reacting them to obtain a tin phosphide-doped hard carbon composite material; (3) coating the surface of the tin phosphide-doped hard carbon composite material with a sodium fast ion conductor composite material to obtain the asphalt-based hard carbon composite material.

5. The preparation method according to claim 4, characterized in that: The tin source in step (1) includes any one of stannous oleate, stannous stearate, stannous oxalate, stannous oxalate, tin pyrophosphate, tin methanesulfonate, dibutyltin diacetate, dioctyltin distearate, tin 2-ethylhexanoate, tributyltin salicylate or tributyltin acetate, or a combination of at least two thereof; The oxidant in step (1) comprises hydrogen peroxide and / or peracetic acid; The organic solvent in step (1) comprises any one of carbon tetrachloride, n-hexane, xylene or carbon disulfide, or a combination of at least two thereof; The mass ratio of the oxidized asphalt, tin source, oxidant and organic solvent in step (1) is 100:(1-10):(5-15):(500-1500); A heteroatom compound is also added during the mixing process of step (1); The heteroatom compound includes any one or a combination of at least two of 4-methylthiosemicarbazide, diaminothiourea or malonylthiourea; The mass ratio of the heteroatom compound to the tin source is (1-10):(1-10).

6. The preparation method according to claim 4, characterized in that: The temperature of the hydrothermal reaction in step (1) is 80-150°C and the time is 1-6h; After the hydrothermal reaction is completed, drying is further performed, and the drying is freeze drying.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The phosphorus source in step (2) is a phosphorus-containing gas, and the phosphorus-containing gas includes red phosphorus gas; The gas flow rate of the phosphorus-containing gas is 100-500 mL / min; The reaction temperature in step (2) is 500-800°C and the reaction time is 60-600 min; After the reaction in step (2) is completed, a cross-linking gas is introduced to perform cross-linking and curing; The cross-linking gas includes any one of peroxide acetic acid gas, cyclohexanone peroxide gas, butanone peroxide gas or lauroyl peroxide gas, or a combination of at least two thereof; The gas flow rate of the cross-linking gas is 100-500 mL / min; The cross-linking curing temperature is 500-800° C. and the time is 60-600 min.

8. The preparation method according to claim 4, characterized in that: The coating method in step (3) includes atomic layer deposition; During the coating process in step (3), the ambient temperature is 300-400°C.

9. The preparation method according to claim 4, characterized in that: The preparation method comprises the following steps: (1) After dissolving the oxidized asphalt in an organic solvent, adding a heteroatom compound and a tin source to disperse uniformly, then dropping an oxidant to mix, performing a hydrothermal reaction at 80-150° C. for 1-6 hours, filtering, and freeze-drying to obtain a tin-doped hard carbon precursor material; Wherein, the mass ratio of oxidized asphalt, tin source, heteroatom compound, oxidant and organic solvent is 100:(1-10):(1-10):(5-15):(500-1500); (2) heating the tin-doped hard carbon precursor material to 500-800° C., introducing a phosphorus-containing gas at a flow rate of 100-500 mL / min for 60-600 min, and then introducing a cross-linking gas at a flow rate of 100-500 mL / min for 60-600 min to obtain a tin phosphide-doped hard carbon composite material; (3) placing the tin phosphide-doped hard carbon composite material in a reaction chamber, evacuating the chamber, and then heating the chamber to 300-400°C, cyclically depositing the sodium fast ion conductor composite material on the surface of the tin phosphide-doped hard carbon composite material to form at least one layer of sodium fast ion conductor composite layer, and cooling the chamber after the cyclic deposition to obtain the asphalt-based hard carbon composite material.

10. A sodium ion battery, characterized in that: The negative electrode of the sodium ion battery includes the asphalt-based hard carbon composite material as described in any one of claims 1 to 3.

Citation Information

Patent Citations

  • NASICON type sodium fast ion conductor material, and preparation method and application thereof

    CN113921779A

  • Biomass alloy doped hard carbon material as well as preparation method and application thereof

    CN118073546A

  • Asphalt-based hard carbon composite material, preparation method thereof, battery negative electrode and battery

    CN118198309A